2014
DOI: 10.5152/tftrd.2014.37074
|View full text |Cite
|
Sign up to set email alerts
|

Is the Transcranial Magnetic Stimulation an Adjunctive Treatment in Fibromyalgia Patients?

Abstract: ÖzetAmaç: Medikal tedaviye dirençli fibromiyalji hastalarında motor korteks alana uygulanan düşük frekanslı tekrarlayıcı transkraniyal manyetik stimülasyonun (tTMS) etkinliğini araştırmak. Gereç ve Yöntemler: Toplam 25 hasta randomize olarak aktif ve plasebo gruplarına ayrılarak çalışmaya alındı. Aktif tTMS grubu için stimülasyon sol primer motor korteks üzerinden motor eşik değerin %90'ı hesaplanarak 1 Hz ve 20 dakika uygulandı. Her seansta 1200 uyarı olmak üzere, iki hafta boyunca toplam 10 seans tedavi uygu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
41
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(43 citation statements)
references
References 29 publications
1
41
1
Order By: Relevance
“…We included 38 new studies in this review. Of these, 12 studies (355 participants) investigated only rTMS (Boyer 2014; Dall'Agnol 2014; de Oliveira 2014; Jetté 2013; Malavera 2013; Medeiros 2016; Nardone 2017; Nurmikko 2016; Tekin 2014; Umezaki 2016; Yagci 2014; Yilmaz 2014), 22 studies (772 participants) investigated tDCS (Ahn 2017; Ayache 2016; Bae 2014; Brietzke 2016; Chang 2017; Donnell 2015; Fagerlund 2015; Hagenacker 2014; Harvey 2017; Hazime 2017; Jales Junior 2015; Khedr 2017; Kim 2013; Lagueux 2017; Luedtke 2015; Mendonca 2016; Ngernyam 2015; Oliveira 2015; Sakrajai 2014; Souto 2014; Thibaut 2017; Volz 2016) one study (36 participants) investigated tDCS and rTMS (Attal 2016), two studies (16 participants) investigated tRNS (Curatolo 2017; Palm 2016) and one study investigated RINCE (Deering 2017, 46 participants). Overall this updated review included 94 studies (2983 participants), with 42 trials of rTMS (1101 participants), 36 trials of tDCS (1073 participants), 11 studies of CES (572 participants), one study (36 participants) of both rTMS and tDCS, two studies of RINCE (137 participants) and two studies of tRNS (36 participants).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We included 38 new studies in this review. Of these, 12 studies (355 participants) investigated only rTMS (Boyer 2014; Dall'Agnol 2014; de Oliveira 2014; Jetté 2013; Malavera 2013; Medeiros 2016; Nardone 2017; Nurmikko 2016; Tekin 2014; Umezaki 2016; Yagci 2014; Yilmaz 2014), 22 studies (772 participants) investigated tDCS (Ahn 2017; Ayache 2016; Bae 2014; Brietzke 2016; Chang 2017; Donnell 2015; Fagerlund 2015; Hagenacker 2014; Harvey 2017; Hazime 2017; Jales Junior 2015; Khedr 2017; Kim 2013; Lagueux 2017; Luedtke 2015; Mendonca 2016; Ngernyam 2015; Oliveira 2015; Sakrajai 2014; Souto 2014; Thibaut 2017; Volz 2016) one study (36 participants) investigated tDCS and rTMS (Attal 2016), two studies (16 participants) investigated tRNS (Curatolo 2017; Palm 2016) and one study investigated RINCE (Deering 2017, 46 participants). Overall this updated review included 94 studies (2983 participants), with 42 trials of rTMS (1101 participants), 36 trials of tDCS (1073 participants), 11 studies of CES (572 participants), one study (36 participants) of both rTMS and tDCS, two studies of RINCE (137 participants) and two studies of tRNS (36 participants).…”
Section: Resultsmentioning
confidence: 99%
“…Where we were unable to obtain this information we placed these records in Studies awaiting classification. One report previously placed in Studies awaiting classification was identified as a full paper and included in this review (Yagci 2014).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations